Investigação sobre o desempenho da regra de negociação de pairs trading utilizando o modelo de mudança de regime no mercado de ações brasileiro - Macedo, Marcos Vagner de Castro (2016)
Among various strategies of financial assets negotiations, The Pair Trading strategy has shown relevance in the academic and professional environment and it’s being used as an important strategy. In the main investment funds in Brazil and around the world. The purpose of this work is to examine the Pair Trading strategy with a statistical bias in order to identify and explore financial assets’ inefficiencies. That present long-term relationship. The rules of negotiation proposed, make the use of Cointegration tests to identify eligible actions’ pairs, in order to apply such strategy, along with the use Markov-switching models to define the negotiation strategy. The main goal is to explorer. Temporary deviations (anomalies) of the long-term relationship equilibrium between assets and diferents Regimes. The model is able to identify the nonlinear structure data and also the first and second conditional moments. The applications along with real data from brazilian financial market indicates that a simple portfolio composed by an unique spread, already overcome some of the principals benchmarks of the market.